Effects of citicoline on level of consciousness, serum level of fetuin-A and matrix Gla-protein (MGP) in trauma patients with diffuse axonal injury (DAI) and GCS≤8 - Shokouhi, Ghaffar; Haghjoo, Amir Ghorbani; Sattarnezhad, Neda; Asghari, Mohammad; Sattarnezhad, Aida; Asghari, Ali; Pezeshki, Arastoo (Ulusal travma ve acil cerrahi dergisi = Turkish journal of trauma & emergency surgery : TJTES, 2014)
Citicoline, a neuroprotective drug, has been suggested to improve level of consciousness, mitigating secondary to brain damage and ectopic vascular calcification, following post-traumatic neurogenesis and angiogenesis, inducing calcification modulators, like fetuin-A and matrix Gla-protein (MGP). This study aimed to investigate effects of citicoline on levels of consciousness, serum levels of fetuin-A and MGP in patients with severe traumatic brain injury. This double blind randomized controlled trial (RCT) was conducted on patients with diagnosis of diffuse axonal injury (DAI) and GCS≤8. The cases were treated with citicoline (500 mg every 6 hours) intravenously for fifteen days. Daily GCS assessment and intermittent blood sampling were done for both cases and controls. Fifty-eight patients were included in the study and during the study period, mean GCS levels improved in both groups; however, the difference was inconsiderable (p>0.05). Serum levels of fetuin-A, a negative phase reactant, increased in the group treated with citicoline (p=0.012), while these changes were insignificant for the controls (p=0.455). Serum levels of MGP, a calcification inhibitor, increased in the cases (p=0.046). The alterations were inconsequential in the control group (p=0.405). The findings of this study suggest neutral effects of citicoline on level of consciousness and GCS. Through increasing levels of fetuin-A and MGP, citicoline may have protective effects against inflammatory damage and vascular calcification secondary to head trauma.